Magnesium and its alloys : technology and applications - Bamberger, Menachem; Dobrzański, Leszek A.; Totten, George E. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"Magnesium alloys are known for their light weight, high specific stiffness, and excellent castability and workability. The use of Mg alloys in general, and in the transportation industry in particular, has significantly increased over the last decades, and in-depth and broad knowledge is essential to meet the diverse mechanical, physical and environmental requirements. The Mg encyclopedia will cover a wide scope of topics related to Mg science and engineering, from manufacturing through production to finishing and applications. It will cover such topics as computational thermodynamics, modern Mg-alloys with enhanced creep or fatigue properties, cutting-edge approaches to melt treating (grain refinement, micro-alloying and the resulting solidification and growth), coatings, surface engineering, environmental protection (recycling and green energy storage and production), as well as biomedical applications"--
The importance of magnesium and its alloys in modern technology and methods of shaping their structure and properties / Leszek A. Dobrzanski, Menachem Bamberger, George E. Totten -- Casting Technologies, Microstructure and Properties / Trevor Abbott -- Magnesium Production from Calcined Dolomite Via The Pidgeon Process / Mehmet Bugdayci.
OCLC-licensed vendor bibliographic record.
Keywords: Magnesium -- Metallurgy; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Material Science